Does It Pay to Disclose CSR Information? Evidence from French Companies - Dardour, Ali; Husser, Jocelyn (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2016)
This article looks at how company disclosure of corporate social responsibility (CSR) information affects executive compensation through an empirical study of a sample of French companies listed on the SBF 120 index from 2007 to 2011. The focus is on short-term incentive compensation and total incentive compensation. These two components are not correlated with the total CSR disclosure score (comprising environmental, social, and governance factors). The study reveals that only the environmental disclosure score is correlated with (short term and total) executive incentive compensation. Social and governance disclosure do not have any effect on executive incentive compensation.